Bitter wind a western story - Overholser, Wayne D. (Waterville, Me. Five Star, 2006)
A hired gun decides to change his ways and settles down at a Wyoming ranch, but soon learns that the choices he made in his past cannot be escaped and will continue to impact his future
"Five Star western"--T.p. veso.
88001
Keywords: Frontier and pioneer life; Ranchers; Wyoming; Western stories